Exploring EFL Teachers’ Classroom Management Approaches and Students Responses to Male and Female Teachers - Riki Bugis; Moh. Saleh Tuharea; Zulkifli Akhmad (Al-Lisan: Jurnal Bahasa, 2021)
The goal of this study is to explore the EFL classroom management approaches and how students respond to classroom management by the male and female English teacher. The subjects of the research were two English teachers and 60 students. This research is based on qualitative research. The data analysis was carried out in three phases: data reduction, data presentation, and conclusions. This study finds four types of classroom management by male English teachers and female English teachers. The first is the seating arrangements, the second is the rules and procedures, the third is the discipline, and the final is the teachers' appearance. Meanwhile, questionnaires and interviews show that there is a positive response to classroom management that has been carried out by English teachers, both male and female.